Glucocorticoid Action on Hybrid Clones Derived from Cultured Myeloma and Lymphoma Cell Lines - Gehring, Ulrich (1972)
Cells of a cloned myeloma line from a Balb/c mouse contain specific cytoplasmic glucocorticoid receptors and are killed by dexamethasone. Cells of a lymphoma line (from mouse strain C57BL) also contain specific glucocorticoid receptors but are resistant to the steroid. Cells of two hybrid clones with widely differing chromosome numbers, derived by fusion between the resistant lymphoma and the sensitive myeloma, contain specific glucocorticoid receptors with similar binding properties as the parental receptors and are killed by dexamethasone. Since the lethal effect of the steroid is expressed in the hybrid cells, failure of the parent lymphoma line to be affected by dexamethasone is probably not due to an inhibitor of the lethal reaction.